PERTANGGUNGJAWABAN PIDANA INDUSTRI FARMASI DAN BPOM TERKAIT PENCEMARAN OBAT CAIR DALAM HUKUM KESEHATAN - Sattvika Putri, Desak Ayu Made Sintya; D. PANJAITAN, ANANDA CHRISNA (Jurnal Yustitia, 2023)
There is negligence of the pharmaceutical industry and BPOM as drug producers and drugsupervisors. Thus causing Atypical Kidney Injury (AKI) in children. Therefore, these parties must beaccountable for their mistakes according to Indonesian Health Law. The formulation of the problem in thisstudy is legal consequences in cases of solvent drug contamination and how is the criminal responsibility ofthe pharmaceutical industry and BPOM related to liquid drug pollution according to health law in Indonesia?This research uses normative legal methods with a statutory approach that is associated with the legalissuesbeing discussed. The legal materials used are primary and secondary legal materials.The results of this study are: first, the criminal responsibility imposed on the pharmaceutical industryis regulated in Article 196 and Article 201 paragraphs (2) and (3) of Law Number 36 of 2009 concerningHealth, then the second for the criminal responsibility of BPOM is regulated in Article 359 and Article 360paragraph (1) of the Criminal Code (KUHP).